Study of energy alternatives based on renewable generation sources for the electrification of isolated systems in the Amazon - Elias Nunes , Eduardo; Ferreira dos Santos Neto , Aldir; Araújo Gonçalo , Thiago; Gondres Tourné , Israel; Cláudio Souza Gomes, Raimundo (Seven Editora, 2023)
T The electric sector in the Amazon needs to diversify fossil fuel supply sources, as well as encourage the use of renewable energy sources, so the project carried out a critical study of energy generation sources and their use to ensure the supply of electricity from an environmentally sustainable way to electrify isolated systems in the Amazon. From this, an art study was carried out on the main sources of renewable energy used in Brazil and the Amazon, characterizing the current costs of electricity generation in these isolated communities, with this it became evident that for these systems the sources of renewable energy generation most viable according to the cost analysis carried out in this work are solar and biomass. DOI: 10.56238/pacfdnsv1-126